Effect of Sales, Production Cost and Operating Cost on Net Profit: Case Study in Cosmetic Companies and Household Good Listed on The Indonesia Stock Exchange - Ningrum, Rafika Resti Astri; Yulia, Iis Anisa; Wahidhani, Eha (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the effect of sales, production cost, and operating costs on net profit either partially or simultaneously. The analytical method used is panel data linear regression with the dependent variable, namely net income, and the independent variables, namely sales, production costs and operating costs. The result of the research show that sales, production cost and operating costs have an effect on net income either particially or simultaneously. Keywords: Sales, Production Costs, Operating Costs and Net Income